2020
DOI: 10.1212/wnl.0000000000009653
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic manifestations in an infant with COVID-19

Abstract: We report the case of a COVID-19-positive 6-week-old who presented with fever, cough, and 2 brief 10-15 seconds episodes of upward gaze and bilateral leg stiffening. CaseA 6-week-old term male infant presented for evaluation after 1 day of cough, fever, and brief episodes of sustained upward gaze associated with bilateral leg stiffening. The initial episode occurred after a diaper change. There was no shaking, breathing change, or pallor during this episode. There was no association with feeding. The infant ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 10 publications
2
117
0
17
Order By: Relevance
“…5 COVID-19 encephalitis may manifest with seizures, as it did in this case report of a 6week old. 8 Patient's EEG showed interictal abnormalities of excessive temporal sharp waves and intermittent delta vertex slowing. One patient in a study of 214 COVID-positive subjects had seizure.…”
Section: Mri Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…5 COVID-19 encephalitis may manifest with seizures, as it did in this case report of a 6week old. 8 Patient's EEG showed interictal abnormalities of excessive temporal sharp waves and intermittent delta vertex slowing. One patient in a study of 214 COVID-positive subjects had seizure.…”
Section: Mri Brainmentioning
confidence: 99%
“…A case report of a COVID-positive 6 week old with a 3-minute event of tonic stiffening and upgaze showed interictal abnormalities on EEG of excessive temporal sharp waves, intermittent delta vertex slowing. 8 A 24 year-old presented in convulsive status epilepticus, found to have COVID-19. CSF OP was 32 and the rest of the CSF analysis was normal.…”
Section: Mri Brainmentioning
confidence: 99%
“…Dugu et al [ 134 ] reported a 6-week-old COVID-19 case presenting with cough, fever, and two brief episodes (10–15 s) of upward gaze and bilateral leg stiffening. McAbee et al [ 66 ] reported an 11-year-old male COVID-19 case with SE and CSF evidence for encephalitis.…”
Section: Cns Manifestations Associated With Covid-19mentioning
confidence: 99%
“…Confirming this low incidence of seizures, no cases of status epilepticus or new onset seizures were reported in a large cohort of over 304 hospitalized patients with COVID-19 in Hubei Province, China, 12 although there have been isolated case reports describing seizures at presentation in both adult and pediatric patients with COVID-19. 13,14 In the series by Mao and colleagues, 11 the patients were subdivided based on the severity of their pneumonia and pulmonary impairment, and among those with "severe" disease (n = 88) the incidence of CNS symptoms was higher (31%) compared to the non-severe group (21%), although the results were not statistically significant (p = 0.09). Although all the categorized CNS symptoms occurred more frequently in patients with severe disease compared to non-severe disease, only impaired consciousness (15% in severe vs 2% in non-severe, p < 0.001) and acute cerebrovascular disease (5.7% vs 0.8%; p = 0.03) were significantly different between the two groups.…”
Section: Neurological Complications Of Systemic Covid-19mentioning
confidence: 99%